PENGARUH PRICE EARNING RATIO (PER), DEBT TO EQUITY (DER), RETURN ON ASSETS (ROA) TERHADAP DEVIDEN PAYOUT RATIO (DPR) PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Khoirina; Evi Meida Sari (Journal of Accounting Taxing and Auditing (JATA), 2022)
The purpose of this study was to determine the effect of Price Earning Ratio, Debt To Equity, Return On Assets Against Dividend Payout Ratio in real estate and property companies listed on the Indonesia Stock Exchange. This study uses descriptive research methods, quantitative research that uses the financial statements of real estate and property companies on the Indonesian stock exchange during the 2016-2019 period and found 45 companies while 5 companies that entered the criteria as samples, the analysis tool used multiple linear regression models. The results of statistical tests show that simultaneously PER, DER ROA have a significant effect on DPR where the adjusted R square is 0.488. partially PER has a significant effect on the DPR, DER has no significant effect on the DPR and Roa has a significant effect on the DPR for real estate and property companies on the Indonesia Stock Exchange Keywords : Price Earning Ratio (PER), Debt To Equity Ratio (DER), Return On Asset (ROA) Devident Payout Ratio (DPR)